FAKTOR-FAKTOR PENENTU TINGKAT PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Sultoni, Hasan (LIPI, 2014)
This study aimed to verify the impact of macroeconomic variables on Islamic commercial bank profitability in Indonesia. Applying the error correction models (ECM), this study involved a sample of 3 Islamic banks which are banks operating throughout the study period and the bank that issued the financial statements during the first quarter of 2006 until the third quarter of 2011. The results showed only a variable interest rate which affects the profitability of Islamic banks in Indonesia. Using the Dickey-Fuller (DF) and Augmented Dickey-Fuller (ADF) test, it is proven that there exists a dynamic relationship (long term cointegration) between gross domestic product, inflation, interest rate, market share, money supply and profitability Islamic commercial banks.